Sustainable development goals under party-led development in Laos - Supitcha Punya (2020)
© 2020, Khon Kaen University. All rights reserved. This article aims to analyze how the Lao government, especially the Lao People’s Revolutionary Party (LPRP), interprets and implements the Sustainable Development Goals (SDGs). Content analysis and documentary method are employed as research methods to analyze the SDGs in Laos. For a socialist country under one-party rule, the SDGs create a dilemma. While they promote development, they also seem to imply a multi-party democracy. This article argues that the LPRP manages to reinterpret the SDGs in such a way that they support the national development agenda without calling for a multi-party system or massive political reform. Thus, the SDGs become another source of the legitimation of the one-party state. To support this argument, the article first deals with the role of external development partners in promoting the SDGs in Lao development. Next, it examines how the Lao leadership interprets and implements the SDGs in national development. The concept of sustainability has been interpreted to be associated with political stability and security in the one-party state, forming the particular fourth pillar of the SDGs in Laos. This pillar allows the LPRP to employ a socialist rhetoric, while at the same time pointing to successful development in compliance with the SDGs to legitimize one-party rule.